2008
DOI: 10.1002/pd.2141
|View full text |Cite
|
Sign up to set email alerts
|

First trimester maternal serum PAPP‐A, β‐hCG and ADAM12 in prediction of small‐for‐gestational‐age fetuses

Abstract: Early prediction of fetuses being SGA is feasible with the combination of first trimester PAPP-A, beta-hCG and ADAM12. Screening performance is approaching clinical relevance. The inclusion of further markers is an attractive option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 41 publications
4
43
0
1
Order By: Relevance
“…The early identification of the fetuses at risk for SGA or LGA is of notable clinical interest; in fact, health resources could be used in a better way and prophylaxis could be done [15,20]. However, even if the association between the levels of PAPP-A and a low neonatal weight has been demonstrated, the sensitivity of such a screening method for the prediction of low birth weight and perinatal complications seems to be rather low (the positive correlation, when present, is moderate: the value of ρ is in the 0.3-0.7 range).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early identification of the fetuses at risk for SGA or LGA is of notable clinical interest; in fact, health resources could be used in a better way and prophylaxis could be done [15,20]. However, even if the association between the levels of PAPP-A and a low neonatal weight has been demonstrated, the sensitivity of such a screening method for the prediction of low birth weight and perinatal complications seems to be rather low (the positive correlation, when present, is moderate: the value of ρ is in the 0.3-0.7 range).…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of IGFs seem to be associated with implantation and placentation disturbances, which could be responsible for reduced fetal growth [3,15,21]. Studies on knockout mice have shown that the IGFs are crucial for correct embryonic development and fetal growth [2].…”
Section: Introduction Biochemical Assumptionmentioning
confidence: 98%
“…ADAM12 has been studied as a first trimester marker for predicting pre-eclampsia [8][10], aneuploidy [8], [10][15] and small-for-gestational age fetuses [16], [17]. A clear biological explanation for the decreased level of ADAM12 in EPs does not exist; however, the predominant theory involving impaired placentation could account for ADAM12 playing an important role in the growth and function of the placenta [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ADAM-12 levels have been shown to decrease in pregnancies which resulted in growth-restricted fetuses, supporting a role of ADAM-12 in fetal growth [30,31] . However, a recent study has found no significant difference in first-trimester maternal serum ADAM-12 concentrations between controls and pregnancies resulting in PE [32] .…”
Section: Adam-12 In Adverse Pregnancy Outcomesmentioning
confidence: 90%